2018
DOI: 10.1097/mcp.0000000000000489
|View full text |Cite
|
Sign up to set email alerts
|

Updates in the diagnosis and treatment of malignant pleural mesothelioma

Abstract: MPM remains difficult to treat and has an overall poor prognosis despite current multimodality treatment. Thoracoscopy with multiple pleural biopsies can provide adequate tissue specimens for diagnostic testing to distinguish histologic MPM subtypes and perform molecular profiling, which influence prognosis and treatment options. In early clinical trials, immunotherapies and therapies directed against cancer-associated antigens and oncogenic alterations are emerging as promising future treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 48 publications
0
15
0
4
Order By: Relevance
“…Italy banned asbestos extraction, use, and commercialization in 1992 (Italian Law 257/92) and it is thus important to monitor the trend of MPM occurrence to detect the effects of such a ban. The large number of MPM cases expected in the next years is of particular concern due to the extremely poor prognosis of this condition and the current lack of effective therapeutic options [20].…”
Section: Introductionmentioning
confidence: 99%
“…Italy banned asbestos extraction, use, and commercialization in 1992 (Italian Law 257/92) and it is thus important to monitor the trend of MPM occurrence to detect the effects of such a ban. The large number of MPM cases expected in the next years is of particular concern due to the extremely poor prognosis of this condition and the current lack of effective therapeutic options [20].…”
Section: Introductionmentioning
confidence: 99%
“…MPM can be of epithelioid, biphasic or sarcomatoid histotype. The sarcomatoid histotype is considered to be most aggressive followed by the biphasic and epithelioid type, irrespective of therapy 4,5 …”
Section: Introductionmentioning
confidence: 99%
“…Among all the mesothelioma patients, the median expression of fibulin-3 and HMGB1 was 4 (3-4) and 7 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12), separately (Fig. 2).…”
Section: Fibulin-3 and Hmgb1 Expression Are Not Different Between Submentioning
confidence: 95%
“…Tumor size, grade, and lymph node status were correlated with prognosis for patients of mesothelioma. Clinical treatments with chemotherapy, surgery, radiation, and novel therapies have been associated with prolonged survival time in mesothelioma patients 10 . Previous studies 11,12 found that BAP1 mutation and Ki-67 index > 5% were associated with prolonged survival time of malignant mesothelioma, based on tissue microarray (TMA) method.…”
mentioning
confidence: 99%